Propuesta de implementación de logística inversa de las aguas agrias de la refinería de Cartagena (2020)
In this document, a proposal is made for the implementation of reverse logistics for sour water at the Cartagena Refinery. In order to achieve its reuse in other processes from a previous treatment with sodium hydroxide or caustic soda. To achieve this objective, a compilation of operational information was initially carried out on the current steam stripping method. In which it was found that for the month of March 2019 the required ammonia concentration (<40ppm) was not met for its use in other units. Following this, the ammonia stripping process with caustic soda was evaluated on a laboratory scale as a method of implementing reverse logistics. For which, samples of the water of exit of the tower offal were taken and soda was used to different concentrations. Whose results, allowed to reach a percentage of ammoniacal nitrogen removal of 96.8%. Finally, an economic evaluation was carried out to compare the processing costs of 249,660,000 gallons of sour water per year for both methods. Where a value of US$ 2,44 × 106 was obtained per steam stripping versus a value of US$ 9,98× 106 using soda # 1 and US$ 19,96× 106using soda # 2. In addition, if the method with soda is implemented, the company would save US$ 28.793,55 × 106 in raw water and US$ 16.488.170,5× 106 for pre-discharge treatments.